Studies on Effects of Renin-angiotensin System on Hemodynamics and Cardiovascular System in Essential Hypertension - Ishimaru, Katuo; Kimura, Masaru (Nihon Jinzo Gakkai shi, 1980)
Angiotensin II (All) (0.075 ng/kg) was infused in 10 normal subjects during 20 seconds. Changes in left ventricular systolic time intervals (LVSTI) measured by mechanocardiography were examined. The LVSTI were QII, left ventricular ejection time and pre-ejection period. Their values were corrected for the heart rate (HR) and abbreviated to QIIc, ETc and PEPc. By response to the infusion of [1-Sar, S-Ileu] All (AIIA) (600 ng/kg/min) during 30 minutes, 10 normal subjects and 26 essential hypertensive patients (EHP) were classified into responder groups (RG) whose diastolic blood pressure (DBP) decreased more than 10 mmHg and others except for RG (non-responder groups : N-RG). Changes in hemodynamics measured by impedance cardiography were examined. By types of plasma renin activity (PRA), 32EHP were classified into high renin- (HRG), normo-renin- (NRG) and low renin groups (LRG). 1) HR decreased, QIIc, PEPc and PEP/ET increased, and systolic blood pressure (SBP) and DBP elevated by All infusion in normal subjects. 2) LVSTI, SBP, stroke volume (SV) and cardiac out-put (CO) didn't change, but DBP and total peripheral resistance (TPR) increased by AIIA infusion in normal subjects. 3) PEPc and PEP, ET were shortened, CO and cardiac index (CI) increased, and TPR decreased by AIIA infusion in RG. QIIc, PEPc, PEP/ET, BP and TPR increased, CO and CI decreased by AIIA infusion in N-RG. 4) To compare the values of the RG and N-RG before AIIA infusion, ETc was shorter, PEPc was longer, PEP/ET and TPR were larger, SV, stroke index, CO and CI were smaller in RG. BP and HR were the same in both groups. These suggested that the increased left ventricular load due to elevation of TPR was already present in RG. 5) To compare the three groups, the HR and QIIc were same, but ETc was the lowest in LRG and the highest in HRG. PEPc and PEP/ET were the highest in HRG and the lowest in LRG. These indicated that the cardiac load increased remarkably in HRG compaed with that in NRG and LRG. 6) Significant correlation was present between PRA and PEP/ET. Accordingly in EHP, LVSTI is available to ascertain if hypertension depends on All or not.